Caudillismo along the Nile. Issue 1 (2nd January 2016) - Springborg, Robert
Abstract: The "coup-volution" of 2011 removed President Mubarak but not his authoritarian regime, which is now guided by his successor, President Abd al Fattah al-Sisi. Both autocrats, there are nevertheless important differences between these two presidents and their respective regimes. Sisi's tougher authoritarianism is analogous to the Latin American prototype of "delegative democracy", a stalled phase of democratic institution-building in which voters delegate their authority to the president, who rules unconstrained by a balance of institutional powers. The primary feature of what in the Egyptian case might better be termed "delegative authoritarianism" is the decision-making autonomy of the president, who perceives himself as the "embodiment of the nation and the main custodian and definer of its interests". This results in erratic, inconsistent and ineffective policymaking, which isolates the president yet more from institutions and political forces, while causing the entire polity to be suffused with a deep cynicism. Although the most probable scenario is that Sisi will continue for the foreseeable future as Egypt's delegative dictator, as a one-man band his regime is inherently unstable and prone to coups, coup-volutions and outright revolutions.